Rare Circulating Cells in Familial Waldenström Macroglobulinemia Displaying the MYD88 L265P Mutation Are Enriched by Epstein-Barr Virus Immortalization. - Maroulio Pertesi; Perrine Galia; Nicolas Nazaret; Maxime Vallée; Laurent Garderet; Xavier Leleu; Hervé Avet-Loiseau; Matthieu Foll; Graham Byrnes; Joel Lachuer; James D McKay; Charles Dumontet (PLoS ONE)
The MYD88 L265P is a recurrent somatic mutation in neoplastic cells from patients with Waldenström Macroglobulinemia (WM). We identified the MYD88 L265P mutation in three individuals from unrelated families, but its presence did not explain the disease segregation within these WM pedigrees. We observed the mutation in these three individuals at high allele fractions in DNA extracted from EBV-immortalized Lymphoblastoid cell lines established from peripheral blood (LCL), but at much lower allele fractions in DNA extracted directly from peripheral blood, suggesting that this mutation is present in a clonal cell subpopulation rather than of germ-line origin. Furthermore, we observed that the MYD88 L265P mutation is enriched in WM families, detected in 40.5% of patients with familial WM or MGUS (10/22 WM, 5/15 MGUS), compared to 3.5% of patients with familial MM or MGUS (0/72 MM, 4/41 MGUS) (p = 10-7). The mutant allele frequency increased with passages in vitro after immortalization with Epstein-Barr virus (EBV) consistent with the MYD88 L265P described gain-of-function proposed for this mutation. The MYD88 L265P mutation appears to be frequently present in circulating cells in patients with WM, and MGUS, and these cells are amenable to immortalization by EBV.